Attitudes and work preferences toward older people among Malay undergraduate nursing students - Syed Elias, Sharifah Munirah; Jaafar, Nor Faeziah; Siew Pien, Lee (Makara Journal of Health Research, 2020)
Background: The aging population is increasing globally and requires a high demand for healthcare services in several countries. As a way of preparing future nurses in aged care, substantial incorporation of gerontology courses in the nursing program to meet future needs is required. The present study aimed to investigate the association between attitudes and work preferences toward older people among undergraduate nursing students. Methods: A cross-sectional study was conducted involving 291 nursing students at a Malaysian public university. A set of questionnaires was used that comprised the following three parts: (1) Part A: Sociodemographic background, (2) Part B: Attitudes toward older people, and (3) Part C: Nursing students’ work preferences. Results: Most of the participants (80.4%) demonstrated slightly positive attitudes on older people. Only 2.4% selected older people group as their work preference. There were no significant associations between attitudes with sex (p = 0.84), year of study (p = 0.30), living status (p = 0.77), and work preferences (p = 0.81). Conclusion: Overall, the majority of participants had slightly positive attitudes on older people. Although they had positive attitudes on older people, working in aged care setting is not their first preference after their graduation.